Hubungan Karakteristik Gambaran Radiografi Toraks Distribusi Lesi Paru dengan Prognosis Pasien COVID-19 - Fransisca Tarida Yuniar Sinaga; Hetti Rusmini; Alfi Wahyudi; Retno Ariza Soeprihatini Soemarwoto; Anse Diana Valentine Messah; Intan Utami Putri (Puslitbang Sinergis Asa Professional, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The transmission rapidly from human to human via aerosol droplets and direct contact, accelerating the spread of SARS-CoV-2 in various parts of the world. Chest radiograph can be used to monitor the development of pulmonary disorders due to COVID-19, a reference for medical personnel in screening for patients who are suspected of being infected to COVID-19, and to study the prognosis of patients COVID-19 as well. The aims of this study was to determine the relationship between the characteristics of the distribution of chest radiograph lesions and the prognosis of COVID-19 patients in Bandar Lampung City in 2020. This study was a descriptive analytic study with a retrospective approach. Analysis of the data used are univariate analysis and bivariate analysis using the Spearman correlation test. The results of statistical tests using the Spearman Correlation Test showed that there was a relationship between the characteristics of the distribution of chest radiograph lesions and the prognosis of patients who were confirmed positive for COVID-19 in Bandar Lampung City in 2020, p-value = 0.001 (r = 0.203 weak relationship) on the chest radiograph features of involvement lung, p-value = 0.002 (r = 0.188 weak relationship) on the chest radiograph distribution of lesions from top to bottom, and p-value = 0.030 (r = 0.135 weak relationship) on the chest radiograph distribution of central to peripheral lesions. The conclusion of this study is that there is a significant relationship between the characteristics of the distribution of chest radiograph lesions and the prognosis of COVID-19 patients in Bandar Lampung City in 2020.